2016
DOI: 10.1590/0074-02760160291
|View full text |Cite
|
Sign up to set email alerts
|

Pyriproxyfen and the microcephaly epidemic in Brazil - an ecological approach to explore the hypothesis of their association

Abstract: The microcephaly epidemic in Brazil generated intense debate regarding its causality, and one hypothesised cause of this epidemic, now recognised as congenital Zika virus syndrome, was the treatment of drinking water tanks with pyriproxyfen to control Aedes aegypti larvae. We present the results of a geographical analysis of the association between the prevalence of microcephaly confirmed by Fenton growth charts and the type of larvicide used in the municipalities that were home to the mothers of the affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 5 publications
1
16
0
5
Order By: Relevance
“…However, as is the case with surveillance in the United States, for example [27], the majority of cases did not have a documented cause and, in the current study, individual etiological investigation is only partially available. Suggestions that maternal vaccination, or the insecticide pyriproxyfen, could be risk factors for microcephaly have not been borne out [25,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…However, as is the case with surveillance in the United States, for example [27], the majority of cases did not have a documented cause and, in the current study, individual etiological investigation is only partially available. Suggestions that maternal vaccination, or the insecticide pyriproxyfen, could be risk factors for microcephaly have not been borne out [25,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Urban hospitals attract populations from a large area [73] and official reporting of cases is not broken down by municipality but rather by state, so that a direct analysis of geographical distribution of exposure to pyriproxyfen is difficult in these particular cases. A recent paper studied the association of microcephaly with the areas of claimed pyriproxyfen use and reports a lack of correlation [74]. If the geographic distribution of use and the reported residences of mothers are confirmed, this study would provide strong evidence against pyriproxyfen as a cause.…”
Section: Use Of Pyriproxyfen In Water Supply In Brazilmentioning
confidence: 74%
“…However, smoking was found to be associated with microcephaly . Similarly, an ecological study found no correlation between the use of the larvicide pyriproxyfen in stored water and microcephaly among municipalities of the metropolitan region of Pernambuco, the epicenter of the Brazilian microcephaly epidemic (Albuquerque et al 2016). Interestingly, experiments in mouse models suggested that maternal diet protein restriction (Barbeito-Andrés et al 2020) and exposure to cyanobacterial saxitoxin through water intake (Pedrosa et al 2019) exacerbate brain malformations induced by ZIKV.…”
Section: Fig 2 Machine Learning Approach and Genetic Czs/microcephamentioning
confidence: 99%